Crises and conversions: the unlikely avenues of "Italian Shiism" - Mirshahvalad, Minoo (Palgrave studies in new religions and alternative spiritualities, 2024)
"This book explores the phenomenon of conversion to Shi'a Islam in Italy. It thoroughly examines the motivations behind this religious transition and scrutinizes the doctrinal characteristics that Shiism incorporates thanks to the contributions of Italian converts. The text emphasizes the significance of René Guénon's Traditionalism as a pivotal factor in driving this religious mobility. Additionally, the book delves into the writings of figures such as Julius Evola, who introduced Guénon to Italy, shedding light on Evola's impact on the youth in the post-World War II era. Furthermore, it evaluates the influence of Henry Corbin on this spiritual journey. To realize this study, between 2018 and 2023, Minoo Mirshahvalad employed multidisciplinary methods that integrated sociology and history." --